A Genome-Wide Association Study Identifies Candidate Genes Associated With Shell Color in Bay Scallop Argopecten irradians irradians - Zhu, Xinghai; Zhang, Junhao; Hou, Xiujiang; Liu, Pingping; Lv, Jia; Xing, Qiang; Huang, Xiaoting; Hu, Jingjie; Bao, Zhenmin (Frontiers in Marine Science, 2021)
Molluscan shell color has consistently drawn attention for its abundant diversity and commercial use in shellfish breeding project. Recently, two new strains of bay scallop (Argopecten irradians irradians) with different shell colors as marked phenotypic trait have been artificially bred to improve their economic values; however, the inheritance mechanism of their shell pigmentation is still unclear. In present study, a genome-wide association study (GWAS) was conducted to determine the genetic basis of shell color in bay scallop utilizing 29,036 high quality single nucleotide polymorphisms (SNPs) derived from 80 purple-red (PP) and 80 black-brown (BP) shell color individuals. GWAS result showed 469 SNPs (p < 1.72E-6) significantly associated with shell color were mainly distributed in chromosome 7. The top three SNPs (chr7-12764003, chr7-13213864 and chr7-11899306) are located in the genic region of G-protein coupled receptor-like 101 (GRL101), Polyketide synthase 1 (PKS1) and Phosphoinositide phospholipase C (PLC1), which have been widely reported to be involved in pigmentation. Successfully, the top three SNPs were verified in another non-breeding bay scallop population. Furthermore, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses obtained 38 GO terms covering 297 genes and aggregating pathways involving 252 annotated genes. Specifically, expression profiles of the top three identified candidate genes were detected in mantles of PP and BP individuals by real-time quantitative reverse transcription PCR. The significantly higher expression levels of GRL101 (6.43-fold) and PLC1 (6.48-fold) in PP, and PKS1 (12.02-fold) in BP implied that GRL101 and PLC1 potentially functioned in purple-red shell coloration, and black pigmentation in BP might be principally regulated by PKS1. Our data provide valuable information for deciphering the phenotype differences of shell color in bay scallop.